Measuring professional competencies of registered nurses and nursing students. A cross-sectional comparative study: Nurses and students’ competencies - Prendi, Emanuela; Stievano, Alessandro; Caruso, Rosario; Duka, Blerina; Spada, Florian; Rocco, Gennaro; Notarnicola, Ippolito (Acta Biomedica Atenei Parmensis, 2022)
Background and Aim of the work: Professional competence is essential in providing nursing care based on standards. This concept can be measured, among various instruments, with the Nurses' Professional Competence Scale Short Form (NPCS-SF). The main aim of this study was to explore the perceptions of Registered Nurses (RNs) and Student Nurses (SNs) of their competencies and investigate their differences in the development of nursing competencies using the Italian version of the NPCS-SF.Methods: A cross-sectional observational study design was accomplished. The research was based on a convenience sample of 328 RNs and SNs (response rate: 81.95%) recruited at the University of Our Lady of Good Counsel, Tirane, Albania and Tor Vergata University Hospital, Rome, Italy.Results: RNs averaged higher than SNs’ (m= 86.11 ± 9.53 SD) in professional competencies development. The factor for which the mean was highest for RNs was ‘ethics of nursing care’ (m = 89.54 ± 8.31 SD). SNs scored the lowest in leadership and coordination of nursing care (m = 78.36 ± 14.55 SD).Conclusions: The factors that scored the highest and lowest on the scale were similar with the results of using NPCS-SF in other countries. The study results may indicate that specific training for RNs and SNs could be accomplished based on different competence factors that show low scores of the NPCS-SF. The NPCS-SF has also shown excellent reliability in the Italian context. Furthermore, these findings have implications for teaching competencies in educational institutions and further research.